The elusive eden : (McGraw-Hill, 2011)
The Elusive Eden charts the historical development of California, beginning with landscape and climate and the development of Native cultures, and continues through the census of 2010 and the election of Jerry Brown to his third term as governor. It portrays a land of remarkable richness and complexity, settled by waves of people with diverse cultures from around the world. Organized in ten parts, each part develops a major theme or issue in the chronological development of the state. The first chapter in Parts II through IX is an in-depth narrative spotlight of an individual or group at a critical moment of change. In Parts I and X, the first chapter helps to place California's whole story in context.